2002
DOI: 10.1046/j.1365-2443.2002.00594.x
|View full text |Cite
|
Sign up to set email alerts
|

Signalling mechanisms in sphingosine 1‐phosphate‐promoted mesangial cell proliferation

Abstract: Background : The bioactive sphingolipid sphingosine 1-phosphate (S1P) is formed by the activation of sphingosine kinase (SPHK) in diverse stimuli, such as platelet-derived growth factor (PDGF). S1P acts not only as an extracellular mediator but also as an intracellular second messenger, resulting in the proliferation of various different types of cells. However, the signal transduction mechanism in S1P-induced proliferation of mesangial cells is poorly known.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
73
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(79 citation statements)
references
References 33 publications
5
73
1
Order By: Relevance
“…In the present study we provide evidence for a novel type of transactivation between GPCRs exemplified by the S1P receptors and the TGF-␤ receptor family. Mesangial cells do express S1P [1][2][3][4][5] (28), and it has recently been suggested that especially S1P 2 and S1P 3 are involved in the mitogenic function of S1P in these cells (28). The authors also propose a crossactivation of the PDGF receptor cascade.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study we provide evidence for a novel type of transactivation between GPCRs exemplified by the S1P receptors and the TGF-␤ receptor family. Mesangial cells do express S1P [1][2][3][4][5] (28), and it has recently been suggested that especially S1P 2 and S1P 3 are involved in the mitogenic function of S1P in these cells (28). The authors also propose a crossactivation of the PDGF receptor cascade.…”
Section: Discussionmentioning
confidence: 99%
“…In renal mesangial cells, several S1P receptors are expressed, including the S1P 1 , S1P 2 , S1P 3 , S1P 4 , and S1P 5 (formerly known as Edg-1, -5, -3, -6, and -8 receptors) (28), which mediate many effects of S1P including mobilization of intracellular calcium, activation of the classical MAPK cascade, and cell proliferation (28).…”
mentioning
confidence: 99%
“…Caspase-3 Activity Assay-The activity of caspase-3 was determined by the EnzChek Caspase-3 Assay Kit (Molecular Probes) following the manufacturer's instructions (12). Briefly, 3 ϫ 10 6 cells were serumstarved for 2 h and treated with the indicated reagents.…”
Section: Methodsmentioning
confidence: 99%
“…DNA Fragmentation Assay-DNA fragmentation was measured using the Cell Death Detection ELISA PLUS kit (Roche Applied Science) following the manufacturer's instructions (12). Briefly, STC-1 cells, cultured in 24-well culture plates, were treated with the indicated reagents.…”
Section: Methodsmentioning
confidence: 99%
“…A balance between Cer and other bioactive metabolites such as sphingosine (Sph) and sphingosine-1-phosphate (S1P) has been pointed out as a sensitive rheostat controlling growth and death of various cell types (14,15). Thus, in contrast to the growth-inhibitory and proapoptotic effects of Cer and Sph (16 -20), S1P has been shown to promote cell growth in various cell types including MC (21,22). Many studies have reported the involvement of sphingomyelinases, the ceramide-generating enzymes, in the regulation of Cer levels in response to proinflammatory cytokines, growth factors, or stress stimuli (23,24).…”
mentioning
confidence: 99%